Surgical treatment of inflammations and adhesions of the abdominal cavity in adolescents using stream hydroscalp - V.V. Skiba; V.F. Rybalchenko; O.V. Ivanko; Yu.G. Demidenko; V.M. Badakh; V.P. Bocharov (Zaslavsky O.Yu., 2017)
The aim of the study was to improve the results of surgical treatment of inflammations and adhesions of the abdominal cavity in adolescents using stream hydroscalpel. Materials and methods. Sixty eight adolescents aged 17-18 years underwent treatment at the surgical department of Kyiv Municipal Clinical Hospital N 1 from 2009 to 2016. There were 39 male (57.35 %) patients, and 29 (42.65 %) - female. Abdominal infiltrates were detected in 52 (76.47 %) patients, and adhesive intestinal obstruction - in 16 (23.53 %). Upon admission to the hospital, clinical blood and urine tests, X-ray and ultrasound study of the abdominal organs were performed. Results. The cause of the inflammatory process was inflammation of the appendix in 49 (72.05 %) individuals and of Meckel's diverticulum - in 3 (4.41 %). The causes of adhesions were appendectomy in the past medical history of 9 males (13.23 %), 5 females (7.35 %); and in two (2.96 %) other female adolescents the cause of the first surgery were gynecological diseases. Hospitalization period: during the first day, there were hospitalized 11 (16.17 %), on the second day - 25 (36.76 %), on the third day - 32 (47.07 %) patients. Upon hospitalization, the general condition was classified as critical in 36 (52.94 %) people, and extremely critical - in 32 (47.06 %), with signs of organ failure - oliguria. Analysis of the clinical picture showed that all 57 (83.82 %) patients had the vomiting syndrome, of them in 29 (42.65 %), vomiting was unbearable, with hiccups. Abdominal pain syndrome has been detected in 63 (92.65 %) patients, of whom in 23 (33.82 %), pain was cramping, and in 40 (58.83 %) - permanent. Pain syndrome was absent in 5 (7.35 %) patients, but they had a feeling of heaviness in the epigastric region. The asymmetry of the anterior abdominal wall is detected in 62 (91.17 %) patients, of them, the asymmetry of the right and left sections - in 34 (50.0 %), and upper and lower - in 28 (41.18 %). In 6 (8.82 %) patients, abdominal cavity wasn't distended, but they had a significant abdominal pain syndrome of cramping nature. X-rays showed that 29 (42.65 %) patients had air-fluid levels. According to ultrasound data, abdominal infiltrates were detected in 52 (76.47 %) individuals, of them in 32 (47.06 %) - in the lower right quadrant, and in 20 (29.41 %) - in the entire right half of the abdomen. In 14 (20.58 %) patients, according to ultrasound examination, it was established the absence of peristalsis in all parts of the intestine, and in 2 (2.95 %) - pendular movements in the left hypochondrium. Free fluid was detected in the pelvic cavity in 23 (33.82 %) patients, and in 31 (45.58 %) - on the right flank. The study found that 12 (17.64 %) persons had atypical clinical symptoms of the disease. All patients were operated using stream hydroscalpel. By separating the inflammatory process, it was found that the cause was the inflammation of the appendix in 49 (72.05 %) and of Meckel's diverticulum - in 3 (4.41 %) patients, the latter has been removed with segmental resection of the colon. The following adhesions were diagnosed: multiple planar in all 16 patients, of which on the background of plane ones, cord-like were detected in 8 patients, and full coverage with volvulus - in 4. Thus, the surgical treatment using stream hydroscalpel for the separation of adhesions has a gentle non-traumatic effect on blood vessels and the intestinal wall in the separation of adhesions and infiltrates that in the future contribute to a more adequate restoration of peristalsis in the early and remote periods after surgery. Two patients due to strangulation required segmental resection of the small intestine in a volume of 25 cm, end-to-end anastomosis was placed with double-row suture. Conclusions. Using the method of direction of infiltrated tissues and adhesions by means of stream hydroscalpel allows precise separation of organ structures and parenchymal organs. Thus, it is possible to minimize blood loss, to prevent damage to anatomical structures and to reduce the time of the surgery.